2020
DOI: 10.1111/tra.12734
|View full text |Cite
|
Sign up to set email alerts
|

Coiled‐coil registry shifts in the F684I mutant of Bicaudal D result in cargo‐independent activation of dynein motility

Abstract: The dynein adaptor Drosophila Bicaudal D (BicD) is auto-inhibited and activates dynein motility only after cargo is bound, but the underlying mechanism is elusive. In contrast, we show that the full-length BicD/F684I mutant activates dynein processivity even in the absence of cargo. Our X-ray structure of the C-terminal domain of the BicD/F684I mutant reveals a coiled-coil registry shift; in the N-terminal region, the two helices of the homodimer are aligned, whereas they are vertically shifted in the wild-typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 66 publications
4
44
0
Order By: Relevance
“…A key step in activating dynein motility is the activation of BicD2 for dynein recruitment, and we and others have recently proposed that cargo-binding activates BicD2 for dynein recruitment by inducing a coiled-coil registry shift in BicD2 (i.e. a vertical displacement of the two α-helices against each other by one helical turn) 26,29,30,60 . In the absence of cargo, BicD2 forms an auto-inhibited looped dimer that cannot recruit dynein, with the CTD masking the Nterminal dynein/dynactin-binding site (NTD) [17][18][19][20][21][22][23][24][25][26][27]67 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A key step in activating dynein motility is the activation of BicD2 for dynein recruitment, and we and others have recently proposed that cargo-binding activates BicD2 for dynein recruitment by inducing a coiled-coil registry shift in BicD2 (i.e. a vertical displacement of the two α-helices against each other by one helical turn) 26,29,30,60 . In the absence of cargo, BicD2 forms an auto-inhibited looped dimer that cannot recruit dynein, with the CTD masking the Nterminal dynein/dynactin-binding site (NTD) [17][18][19][20][21][22][23][24][25][26][27]67 .…”
Section: Discussionmentioning
confidence: 99%
“…S8 and ref. 60 ). Based on these data, we estimate that the α-helical content increases by 14 ± 5 % upon Nup358/BicD2 complex formation, confirming a structural transition from random coil to α-helix.…”
Section: Spectroscopy Confirms Formation Of An α-Helix In Nup358 Upon Binding To Bicd2mentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of oocyte specification has also been observed upon loss of function of BicD (Dienstbier et al, 2009). Therefore, to determine the role of BicD in crb mRNA transport we used BicD 1 , which encodes a constitutively active protein, that binds to Dynein independent of the RNA cargo (Cui et al, 2020) and BicD 2 , shown to behave similar as BicD 1 (Larsen et al, 2008;Liu et al, 2013;Vazquez-Pianzola et al, 2014;Vazquez-Pianzola et al, 2017). crb mRNA in BicD 1 and BicD 2 heterozygous and BicD 1 /BicD 2 transheterozygous egg chambers appeared to be more tightly localised to the posterior end of the oocyte (Suppl.…”
Section: Egl and Intact Microtubules Are Required For Proper Crb Mrnamentioning
confidence: 99%